Kajian Feminisme: Analisis Perbandingan Ideologi “Cantik” Tokoh Perempuan Pada Dua Chick-lit; The Debutante Divorcéé (Janda-Janda Gres) Karya Plum Sykes dan Test Pack Karya Ninit Yunita - R. Myrna Nur Sakinah (Al-Tsaqafa : Jurnal Ilmiah Peradaban Islam, 2017)
This research discusses two chicklit to compare, Translation chicklit and Indonesian chicklit, The Debutante Divorcéé by Plum Sykes dan Test Pack by Ninit Yunita. Both of them have strength to find “beautiful” ideology. The different of “beautiful” ideology in both texts be influenced by popular culture of position and status as woman’s imagery. This research disscusses about Cixousan feminism. From this analysis found that “beautiful” ideology in both texts representated in different form of love.